Diseases of blood and endocrine system in children : the collection of test tasks - Lezhenko, G. O.; Reznichenko, Yu. G.; Pashkova, O. E.; Hyria, O. M.; Kamenshchyk, A. V.; Lebedinets, O. M.; Gladun, E. V.; Sidorova, I. V.; Леженко, Геннадій Олександрович; Резніченко, Юрій Григорович; Пашкова, Олена Єгорівна; Гиря, Олена Максимівна; et al. (ZSMU, 2016)
Pediatrics is one of important clinical disciplines, without deep knowledge of which the forming of modern specialist-physician is not possible. Pediatrics as educational discipline is based on students knowledge of substantive provisions of anatomy, histology, physiology, physiopathology, pathoanatomy, propedeutics and infectious diseases Acquisition of thorough knowledges and abilities from paediatrics allows to utillize them for the savation of clinical problems of diagnostics, prophylaxis and treatment of diseases. Educational and methodical manual “Diseases of blood and endocrine system in children” for the 5 year students of medical faculty compiled in accordance to “Educational profesional programm for high education” after professional direction of „Medicine”, ratified by the Ministries of Education and Health of Ukraine. In developing of materials the long-term experience of pediatrics department of Zaporizhzhia State Medical University and the recommendations of supporting department of pediatrics is used (hospital pediatrics department of National Medical University). Materials given in the Manual show by itself the guidance on the practical classes leadthrough for the 5 year students of medical faculty studying on speciality of Pediatrics and General Practitioner. Taking into account progressive development of pediatrics, change of requirements to the specialists the given educational methodical Manual will incompletely reflecs to the pedagogical and professional necessities, that is why will be perfected and complemented.
Keywords: blood; endocrine system; children; test tasks